LEVANTAMENTO DE MACROINVERTEBRADOS BENTÔNICOS EM UM CORPO HÍDRICO NO MUNICÍPIO DE AQUIDAUANA-MS - SIMPLICIO, Viviane dos Santos; ANDREATTA, Mayene Pereira; MENEZES, Rayane Aparecida Silva; RIBEIRO, Eliane Alves; CORREA, Jonas de Sousa (ANAIS DO ENIC, 2020)
-